2016
DOI: 10.1016/j.ijrobp.2015.11.030
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Early Mortality in Patients Treated With Concurrent Chemoradiation Therapy for Locally Advanced Non-Small Cell Lung Cancer

Abstract: This analysis identified several risk factors associated with early mortality and suggests that future research in the optimization of pretreatment pulmonary function and/or functional lung avoidance treatment may alter the therapeutic ratio in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 19 publications
5
36
1
Order By: Relevance
“…First, the prognostic parameters used in the construction of our nomograms involved typical routine clinical data. More advanced clinical parameters that are prognostic of survival such as tumor size [ 24 ], FEV1 [ 25 ], lymphatic permeation [ 26 ], lymphovascular invasion [ 27 ], and molecular factors [ 23 ] were not included in the design of our nomogram because there were too few incomplete clinical data. An advantage of using basic low-cost clinical parameters is that the data will be widely available, which simplifies performing multicenter studies.…”
Section: Discussionmentioning
confidence: 99%
“…First, the prognostic parameters used in the construction of our nomograms involved typical routine clinical data. More advanced clinical parameters that are prognostic of survival such as tumor size [ 24 ], FEV1 [ 25 ], lymphatic permeation [ 26 ], lymphovascular invasion [ 27 ], and molecular factors [ 23 ] were not included in the design of our nomogram because there were too few incomplete clinical data. An advantage of using basic low-cost clinical parameters is that the data will be widely available, which simplifies performing multicenter studies.…”
Section: Discussionmentioning
confidence: 99%
“…This should also hold true for second and third generation TKIs as these drugs still result in acquired drug resistance through a combination of pre-existing and acquired mutations (5,6), despite overcoming the EGFR T790M mutation which has indeed resulted in superior PFS compared to first generation TKIs (2) Our result that shorter induction times lead to better outcomes contradicts expectations in current multimodal trial protocols for LA-NSCLC, but reflects the increasing risk of TKI resistance as a function of TKI exposure. Induction before CRT has several benefits, most notably decreasing tumor size, which has been shown to improve overall survival when treated with CRT (36,37) and may also lead to surgical candidacy as outlined in the ASCENT trial protocol. But, upfront TKI exposure in advanced staged patients has resulted in a 50-75% average volume change (1), which is similar to the expected surviving fraction after a single 2 Gy radiation fraction (SF2Gy) in NSCLC (38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in-vitro studies have demonstrated an enhance radiosensitivity of EGFR mutant NSCLC compared to WT (28), and so in our model unique radiosensitivity distributions were defined for WT and EGFR mutant populations separately and optimized against FFLF. Distant metastases have been observed to be the most common form of recurrence with a 2 yr. FFDF in the range of [31][32][33][34][35][36][37][38][39][40][41][42][43] % with no statistically significant relationship to EGFR status (22,26,27). Therefore, a common metastatic fraction and growth rate distribution were defined for both populations and optimized against FFDF, as shown in Fig.…”
Section: Model Calibration For Predicting Local and Distant Recurrencmentioning
confidence: 99%
“…In a recent multiinstitutional analysis of 1,245 patients in 13 centres, 10% of patients died within 180 days of treatment (15). Multivariable analysis identified tumor bulk (GTV ≥100 cc: odds ratio 2.61, 95% CI, 1.10-6.20) and pulmonary function (FEV1 <80% predicted: odds ratio 2.53, 95% CI, 1.09-5.88) as predictive factors for early mortality.…”
Section: Controversies On Lung Cancer: Pros and Consmentioning
confidence: 99%